2019
DOI: 10.3390/en12163055
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Profitability Analysis of a Prospective Pennycress to Sustainable Aviation Fuel Supply Chain in Southern USA

Abstract: This study evaluates biorefinery bio-oil feedstock costs at the plant gate for a prospective field pennycress (Thlaspi arvense L.) to sustainable aviation fuel (SAF) supply chain. The biorefinery would supply SAF to the Nashville, Tennessee international airport. Supply chain activities include pennycress production, transporting oilseed to a crushing facility, processing of oilseed into bio-oil, and transporting bio-oil to the biorefinery. The analysis shows profit potential for economic agents in the prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…The sample was divided into five price levels with 20% of the farmers being offered one of these price points ($0.11, $0.22, $0.33, $0.44, or $0.55/kg). The offered price or bid levels were based on estimated breakeven price ranges for pennycress [8].…”
Section: Survey and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample was divided into five price levels with 20% of the farmers being offered one of these price points ($0.11, $0.22, $0.33, $0.44, or $0.55/kg). The offered price or bid levels were based on estimated breakeven price ranges for pennycress [8].…”
Section: Survey and Data Collectionmentioning
confidence: 99%
“…these price points ($0.11, $0.22, $0.33, $0.44, or $0.55/kg). The offered price or bid levels were based on estimated breakeven price ranges for pennycress [8]. The farmers were also asked how many hectares they would produce if they agreed to the price offered and their interest in signing a contract for pennycress production.…”
Section: Survey and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tanzil et al (2021) found that hydroprocessed esters and fatty acids (HEFA) is the most competitive current technology for SAF production compared to five lignocellulosebased technologies evaluated. While SAF production volume in the US is still limited, several biorefineries are producing it at demonstration, pilot, and commercial scale (Trejo-Pech et al, 2019;Khanal and Shah, 2021;Tanzil et al, 2021). One of the current challenges is to produce SAF at prices competitive with fossil-based jet fuel.…”
Section: Introductionmentioning
confidence: 99%